O simbolismo hierofânico das águas : uma análise comparativa entre os romances Mar Morto, de Jorge Amado, e Um Rio Chamado Tempo, uma Casa Chamada Terra, de Mia Couto - Bertasso, Amarildo (2022)
The symbolism of the waters is the subject of this work. The objective of this dissertation is to examine the works Mar Morto, by Jorge Amado, and Um rio chamado tempo, uma casa chamada terra, by Mia Couto, from a comparative perspective, seeking to identify similarities and differences between the two realities, especially with regard to the water symbolism. Comparative literature admits the purpose of seeking confluences between writers, in this case, Jorge Amado, a Brazilian writer, and Mia Couto, a Mozambican writer, as well as covering the mythical narratives of their works. Based on the assumptions of comparative literature, it reflects on the Brazilian and Mozambican literary context with regard to the hierophanic symbolism of water in the novels Mar morto and Um rio chamado tempo, uma casa chamada terra. It is argued that there are significant confluences in the aforementioned works with regard to water and its symbologies, considering that in both novels the narrators present us with this intense relationship of the characters with the water element and everything that derives from it. As a theoretical contribution, are used studies developed by Mircea Eliade (2012, 2016, 2018, 2019), Piazza (1983), Abdala Junior (2003), Prandi (2001), Bachelard (2018), Carvalhal (2006), Candido (2017), Chevalier and Gheerbrant (2003), among others, to better support the analyzes undertaken. Considering the narratives of Jorge Amado and Mia Couto, it was evidenced an association between the hierophanies of the waters of the sea in Mar morto and the Madzimi River in Um rio chamado tempo, uma casa chamada terra, which also work as subversions of the realities presented in each of the novels.